Applied Thermodynamics for Process Modeling in Catalytic Gas Phase Olefin Polymerization Reactors. Issue 1 (15th October 2019) - Bashir, Muhammad Ahsan; Kanellopoulos, Vasileios; Al‐haj Ali, Mohammad; McKenna, Timothy F.L.
Abstract: The Sanchez–Lacombe Equation of State (SL EoS) is used to model the solubility of different industrial alkane penetrants in polyethylene to explain the importance of considering different diluents for different processes, and the impact that this choice can have on operating conditions, especially for the production of linear low density polyethylene (LLDPE). Extension of this approach to ternary (ethylene/penetrant/LLDPE) systems shows the effect of composition of penetrant/ethylene mixtures on the solubility of such mixtures in LLDPE and swelling of the polymer phase at conditions of industrial relevance. This analysis reveals that using a constant polymer density instead of that predicted by the SL EoS can result in erroneous calculations of the particle size distribution developments in an olefin polymerization reactor. Abstract : The importance of correctly estimating the level of particle swelling during the polymerization of olefins in gas phase reactors is demonstrated. It is shown that poor predictions of the particle size and particle size distribution will result from ignoring the complex thermodynamic interactions between the polymer and multiple penetrants and using a constant polymer density instead.